Enterprise information systems concepts, methodologies, tools and applications - Information Resources Management Association (Hershey Business Science Reference, 2011)
"This three-volume collection provides a complete assessment of the latest developments in enterprise information systems research, including development, design, and emerging methodologies"--Provided by publisher.
"Premier reference source" -- Cover.
Includes bibliographical references and index.
Keywords: Management information systems; Information technology -- Management; Electronic commerce; Electronic books; Business enterprises -- Computer networks